A New Privacy-Preserving Scheme for Continuous Query in Location-Based Social Networking Services - Eric Ke Wang; Yunming Ye (International Journal of Distributed Sensor Networks, 2014)
With continuous queries that are used widely in location based mobile social networking services, how to protect the location privacy effectively for continuous query has been a hot topic for researchers. In this paper, we analyze the existing location privacy protection systems and algorithms for location based services; considering their disadvantages of slow responding time and high anonymization costs, we propose a new enhanced greedy cloaking algorithm which predicts a cloaking area at the initial query to be the cloaking region in the whole query lifetime by the comprehensive computation of privacy monitor, quality monitor, and dynamic adjuster. Privacy monitor and quality monitor charge the privacy protection level and service quality degree respectively; dynamic adjuster can adjust the cycle center point dynamically. We employ cycle as cloaking region form which can effectively alleviate the computation overhead. And we compare it with the earlier algorithm on three aspects. The experimental result shows that the enhanced greedy cloaking algorithm is better than the original greedy algorithm on average responding time or anonymization cost.